Phenotypic spectrum of polycystic ovary syndrome and their relationship to the circadian biomarkers, melatonin and cortisol. Issue 3 (22nd March 2019) - Lim, Audrey J. R.; Indran, Inthrani R.; Kramer, Michael S.; Yong, Eu‐Leong
Summary: Objective: Firstly, to investigate whether polycystic ovary syndrome (PCOS) shows a continuum of severity with increasing number of phenotypic features comprising the Rotterdam criteria for PCOS and secondly, to explore relationships of these phenotypes to the circadian biomarkers, cortisol and melatonin. Background: Studies characterizing the spectrum of PCOS subphenotypes give little emphasis to the distinction among women who manifest zero, one or two of the three phenotypic features comprising the Rotterdam criteria. The relationship of circadian biomarkers to PCOS phenotypes is unclear. Design: Cross‐sectional study of 321 participants from 2011 to 2016 conducted at the National University Hospital (NUH), Singapore. Participants: Participants included women who attended a health screen for NUH staff, volunteers from the university community, and women referred for possible PCOS from gynaecological clinics at NUH and KK Women's and Children's Hospital (Singapore). Methods: All participants underwent a physical examination, ovarian ultrasound scan and follicular‐phase blood testing, and completed a health and lifestyle questionnaire. Results: A significant positive linear trend in all clinical and biochemical characteristics of PCOS with increasing number of phenotypic features comprising the Rotterdam criteria. We observed a similar trend in serum cortisol and melatonin, two biomarkers of the circadian rhythm. Conclusion: PCOS may not be an "all‐or‐none" condition, but rather a continuous spectrum. The positive relationship between number of PCOS criteria with melatonin and cortisol merits further investigation on the role of circadian biorhythms in the pathogenesis of PCOS. Abstract : PCOS may not be an "all‐or‐none" condition, but rather a continuous spectrum. The positive relationship between number of PCOS criteria with melatonin and cortisol merits further investigation on the role of circadian biorhythms in the pathogenesis of PCOS.